A Decision Support Methodology for the Design of Reconfigurable Assembly Systems. Issue 11 (2018) - Colledani, M.; Yemane, A.; Lugaresi, G.; Frigerio, N.; Borzi, G.; Bassi, A.; Callegaro, D.
Abstract: The design phase of assembly systems under uncertain product-mix and product volume settings is challenging for both manufacturers and researchers. One of the design paradigms to deal with uncertain and dynamic environments is through reconfigurable system designs. This paper presents the formulation and a solution approach for supporting the design of assembly systems that are based on reconfigurable and modular resources. The method assists manufacturers in the search of optimal design solutions and future reconfiguration actions. Systems designed this way can efficiently respond to external changes, such as evolving product types and uncertain demand scenarios. The proposed methodology has been used to solve a real use-case in the ReCaM project, and preliminary results demonstrate its potential benefits for industrial settings.